2008
DOI: 10.1002/cbic.200700533
|View full text |Cite
|
Sign up to set email alerts
|

Triplex Formation by Pyrene‐Labelled Probes for Nucleic Acid Detection in Fluorescence Assays

Abstract: Triplex-forming homopyrimidine oligonucleotides containing insertions of a 2'-5' uridine linkage featuring a pyrene moiety at the 3'-position exhibit strong fluorescence enhancement upon binding to double-stranded DNA through Hoogsteen base pairing. It is shown that perfect matching of the new modification to the base pair in the duplex is a prerequisite for strong fluorescence, thus offering the potential to detect single mutations in purine stretches of duplex DNA. The increase in the fluorescence signal was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 38 publications
0
22
0
Order By: Relevance
“…As regular nucleobases are virtually nonfluorescent, fluorescence has to be introduced into the third strand. Various protocols were developed to probe triplex melting by fluorescence: 1) fluorescent dyes (pyrene) were linked to the triplex, [26,35] 2) the third strand of the 5'-terminus of an oligonucleotide was not labelled with a fluorescent dye but with a quencher, while the purine-rich strand contained a fluorescent dye nearby the quencher, [37] 3) a fluorescence dye was used in intercalator displacement experiments, [38] and 4) base surrogates such as a fluorescent 2'-deoxyuridine with an annealed naphthalene moiety were employed, [39] or the fluorescent 2-aminopurine 2'-deoxyribonucleoside was used instead of 2'-deoxyadenosine within the antiparallel dA-dT-dA triplex motif. [40] To the best of our knowledge, no fluorescent analogue of protonated dC was employed within the dCH + -dG-dC triad.…”
Section: Triplexmentioning
confidence: 99%
“…As regular nucleobases are virtually nonfluorescent, fluorescence has to be introduced into the third strand. Various protocols were developed to probe triplex melting by fluorescence: 1) fluorescent dyes (pyrene) were linked to the triplex, [26,35] 2) the third strand of the 5'-terminus of an oligonucleotide was not labelled with a fluorescent dye but with a quencher, while the purine-rich strand contained a fluorescent dye nearby the quencher, [37] 3) a fluorescence dye was used in intercalator displacement experiments, [38] and 4) base surrogates such as a fluorescent 2'-deoxyuridine with an annealed naphthalene moiety were employed, [39] or the fluorescent 2-aminopurine 2'-deoxyribonucleoside was used instead of 2'-deoxyadenosine within the antiparallel dA-dT-dA triplex motif. [40] To the best of our knowledge, no fluorescent analogue of protonated dC was employed within the dCH + -dG-dC triad.…”
Section: Triplexmentioning
confidence: 99%
“…Furthermore, Van Daele et al have reported the incorporation of a 3'-pyrene-functionalized thymidine monomer into ONs through 2'-5' linkage; this led to pH-dependent pyrene fluorescence intensity increases upon duplex formation. [11] We have previously reported the synthesis of unlocked nucleic acids (UNAs, 2',3'-seco-RNAs), acyclic RNA analogues in which the ribose ring's C2'ÀC3' bond is absent. [14] Incorporation of UNA components into DNA or RNA additively decreases the thermal stabilities of nucleic acid duplexes.…”
Section: Introductionmentioning
confidence: 99%
“…[5] Pyrene is a chromophore abundantly used in fluorescently labeled ONs because of its long fluorescence lifetime, its high sensitivity toward the surrounding microenvironment, [6] and its ability to stabilize a DNA duplex either through intercalation or groove interactions. [7] Examples of incorporation of pyrene into ONs include conjugation to the nucleobase components, [8] as a replacement for the natural nucleobases, [9] conjugation to the 2'-, [10] 3'-, [11] and 4'-positions of the sugar ring, [12] and in the form of non-nucleosidic incorporations. [13] One sought-after property of a fluorescently labeled ON is the ability to generate a large shift in fluorescence intensity upon hybridization to complementary DNA or RNA, to enable the design of probes capable of detecting specific nucleic acid sequences in homogenous fluorescence assays.…”
Section: Introductionmentioning
confidence: 99%
“…Triplex-based fluorescent probes which exhibit changes in fluorescence intensities or wavelengths upon hybridization with a double-stranded DNA have been reported to detect a DNA triplex formation or facilitate the analysis of the thermal stability of DNA triplexes. [6][7][8][9][10][11][12][13][14] Although the probes utilizing Förster resonance energy transfer (FRET) such as molecular beacons could control the emission of the fluorescence, they normally require two kinds of dyes, a fluorophore and quencher, and an extra structure in addition to the sequencerecognition moiety. [6][7][8][9] In contrast, the probes labeling with a single kind of dye have advantages in the facile synthesis and design.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9] In contrast, the probes labeling with a single kind of dye have advantages in the facile synthesis and design. [10][11][12][13][14][15] Pyrimidine TFOs labeled with thiazole orange (TO) exhibited comparably larger changes in fluorescence intensities before and after triplex formation 14,15 because the fluorescence intensity of TO molecules is low in the presence of poly-pyrimidine singlestranded DNA 16 and high in the presence of DNA triplexes. 15,17 To suppress the fluorescence of the TO molecules covalently attached to DNA oligonucleotides, the utilization of excitonic interaction between two molecules of TO is effective.…”
Section: Introductionmentioning
confidence: 99%